O dualismo cidade e campo em Central do Brasil: uma análise da reelaboração da identidade nacional à luz das teorias pós-modernas - Calhado, Cyntia Gomes (2013)
This dissertation examines the re-elaboration of the national identity, especially in the form of the dualism city-countryside, performed in the film Central do Brasil (Walter Salles, 1998), from the postmodern theory. Acknowledges the centrality of the concept of national identity and the development of the dualism city-countryside in modern Brazilian culture to the incorporation of the subject at different times of national cinema. The study of the recurrence of this dualism in the texts and films about national identity is realized based on Nísia Lima (1999), Mauricio Gonçalves (2011), Celia Tolentino (2001), Ivana Bentes (2007), Ismail Xavier (2007, 2012) and Lúcia Nagib (2006). To spot the similarities between the film and the postmodern esthetic, reflections of Frederic Jameson (1983, 1996, 1998), David Harvey (2005), Renato Pucci Jr. (2008), Lúcia Santaella (2000, 2003), Robert Stam (2005, 2010) and Ronaldo Brito (2001, 2005) are used. A semiotic analysis of the corpus is based on the definitions of Ismail Xavier (2003), Luiz Zanin Oricchio (2003), Lucia Nagib (2003, 2006) and Ivana Bentes (2007). The following aspects are identified: the postmodern aesthetic procedures that the object articulates, as the profusion of quotes with direction reversal that work as trademarks of distancing anti-illusionist, the overburden resource, metalinguistic aspects, negation of the dichotomy erected by modernism between high culture and mass culture - the Great Divide theorized by Andreas Huyssen (1986) - in addition to its stylistic hybridity, as the film blends social drama, melodrama, documentary aspects and road movie in a plot that follows the codes of a moral parable of biblical inspiration. Among the postmodern thematic aspects of Central do Brasil, this dissertation focuses on the way the film draws the parameters of denial of totalization, the utopias and teleology in script and in character development that occur, for example, in the approach that values the individuality instead of collectivity and not explicitly thematizes the sociopolitical forces that focus on the characters, assuming it only as subtext